Adsorption of Methyl Violet Dye from Aqueous Solution by Iraqi Bentonite and Surfactant – Modified Iraqi Bentonite - Mohammed, Suhad Shaker; Al-Heetimi, Dhafir T.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Natural bentonite (B) mineral clay was modified by anionic surfactant sodium dodecyl sulfate (SDS) and characterized using different techniques such as: FTIR spectroscopy, scanning electron microscopy (SEM) and X-Ray diffraction (XRD). The bentonite and modified bentonite were used as adsorbents for the adsorption of methyl violet (MV) from aqueous solutions. The adsorption study was carried out at different conditions such as: contact time, pH value and adsorbent weight. The adsorption kinetic described by pseudo– first order and pseudo – second order equilibrium experimental data described by Langmuir, Freundlich and Temkin isotherm models. The thermodynamic parameters standard free energy ( ), standard entropy ( ) standard enthalpy ( ) were investigated and determined.